A Multifunctional Nanocrystalline CaF2:Tm, Yb@mSiO2 System for Dual‐Triggered and Optically Monitored Doxorubicin Delivery. (20th October 2016) - Li, Yangyang; Zhou, Yurong; Gu, Tongxu; Wang, Gang; Ren, Zhaohui; Weng, Wenjian; Li, Xiang; Han, Gaorong; Mao, Chuanbin
Abstract : Daunting challenges in investigating the controlled release of drugs in complicated intracellular microenvironments demand the development of stimuli‐responsive drug delivery systems. Here, a nanoparticle system, CaF2 :Tm, Yb@mSiO2, made of a mesoporous silica (mSiO2 ) nanosphere with CaF2 :Tm, Yb upconversion nanoparticles (UCNPs) is developed, filling its mesopores and with its surface‐modified with polyacrylic acid for binding the anticancer drug molecules (doxorubicin, DOX). The unique design of CaF2 :Tm, Yb@mSiO2 enables us to trigger the drug release by two mechanisms. One is the pH‐triggered mechanism, where drug molecules are preferentially released from the nanoparticles at acidic conditions unique for the intracellular environment of cancer cells compared to normal cells. Another is the 808 nm near infrared (NIR)‐triggered mechanism, where 808 nm NIR induces the heating of the nanoparticles to weaken the electrostatic interaction between drug molecules and nanoparticles. In addition, luminescence resonance energy transfer occurs from the UCNPs (the energy donor) to the DOX drug (the energy acceptor) in the presence of 980 nm NIR irradiation, allowing us to monitor the drug release by detecting the vanishing blue emission from the UCNPs. This study demonstrates a new multifunctional nanosystem for dual‐triggered and optically monitored drug delivery, which will facilitate the rational design of personalized cancer therapy. Abstract : A multifunctional CaF2 :Tm, Yb@mSiO2 nanoparticle system, made of a mesoporous silica (mSiO2 ) nanosphere filled with CaF2 :Tm, Yb nanocrystals and modified with polyacrylic acid capable of binding the anticancer drug molecules (doxorubicin, DOX), enables to trigger the release of DOX by pH control and NIR irradiation, and to monitor the drug release by detecting the blue emission at ≈478 nm.